Representing the unrepresentable: an exploration of gendered experiences of mental disorder - Futcher, Charis Catheryn (Rhodes University, Faculty of Humanities, Department of Fine Art, 2017)
Inspired by personal lived experiences of mental disorder; this thesis attempts to explore the representation of these complex conditions as they are deeply embedded in trauma, guilt, and stigma. The accompanying exhibition, The Inheritance, figures my own tendencies to contain and conceal my disorder, through the assembling of sculptural containers and their disordered contents. The work, presented as something surreal, comments on the complexities of being a woman with a disorder, as well as on the disease I experience in relation to a history of patriarchal ideologies and psychiatric containment that has informed understandings of 'female madness'. Grounded in my interests in abjection and containment, the artistic processes of trying to express deeply personal experiences of distress allow for the resurfacing of underlying trauma, in regards to the memory of my mother's struggle with Bipolar disorder and her subsequent estrangement. Instead of catharsis, the exhibition represents an inevitable failure to represent the unrepresentable, an experience inextricably bound to the history of gendered oppression and the repression of subjectivity by dominant powers of belief and control. Through my practice as research, I have ultimately grappled with my reluctance to represent my experience, precisely because the topic of mental disorder, though pervasive, is lived and felt by varying groups of people in different ways. As such, my intention is to avoid a reductive and narrow framing of what mental disorder entails. Similarly, I aim to avoid restrictive and presumptuous definitions of gender "“ recognizing that, historically, femininity is a contested category that has silenced many individuals who are not white, heterosexual or gender conforming. My literary research has been limited by these norms and silences, in that most texts detailing the historical visual treatment of disordered subjects fail to recognise the possibility of gender categories that transcend the binary masculinity and femininity. With these limitations in mind, my practice has allowed me to reflect upon the distress of generations of people who have been pathologised based on gender.
Keywords: Mental illness in art; Women -- Mental health; Art, -- South African -- 21st century -- Exhibitions; Sculpture, -- South African -- 21st century -- Exhibitions; Women in art